Money Creation in Fiat and Digital Currency Systems - Gross, Marco; Siebenbrunner, Christoph (Washington, D.C. : International Monetary Fund, 2019)
To support the understanding that banks' debt issuance means money creation, while centralized nonbank financial institutions' and decentralized bond market intermediary lending does not, the paper aims to convey two related points: First, the notion of money creation as a result of banks' loan creation is compatible with the notion of liquid funding needs in a multi-bank system, in which liquid fund (reserve) transfers across banks happen naturally. Second, interest rate-based monetary policy has a bearing on macroeconomic dynamics precisely due to that multi-bank structure. It would lose its impact in the hypothetical case that only one ('singular') commercial bank would exist. We link our discussion to the emergence and design of central bank digital currencies (CBDC), with a special focus on how loans would be granted in a CBDC world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet